Golden1000 Android-Based Application Development Model for Stunting Prevention - Imaniar, Melsa Sagita; Nurdianti, Dewi; Nuraini, Irma (EMBRIO: Jurnal Kebidanan, 2024)
Stunting is a condition in which toddlers have a length or height that is less than their age, occurring due to malnutrition in the first 1000 days of life (HPK). An effort to answer this problem is the existence of the golden1000 application, which is an android-based application that can be used by pregnant women, breastfeeding mothers, mothers with children under 24 months, and midwives in escorting 1000 HPK. The research method used is to analyse user needs, design, algorithms, implementations, and application testing. The results of the research obtained the features needed in the application, including the log-in menu, register, pregnancy, breastfeeding, MP-ASI, articles, child interaction, videos, online consultations, photo albums, agendas, and log-out. The Golden1000 application has a feature that displays educational needs for pregnant women, breastfeeding mothers, and mothers with 2-year-old children, and midwives to escort 1000 HPK to prevent stunting.